Orthopedic polycentric hinge - Popp, William J; McKaskle, Dennis (2007)
A hinge for orthopedic braces includes a pair of support arms, a pair of pivot pins and a hinge plate. The arms are coupled to the hinge plate through the pivot pins and are rotateable between an extension position and a flexion position. The hinge plate has a plurality of adjustment apertures for selective reception of an extension limit pin and a flexion limit pin to selectively restrain rotation of the arms beyond an extension limit and a flexion limit. The pins are retained on the hinge by flexible retainers and are individually positionable among the apertures to adjust the range of motion of the arms. A pair of cover elements pivotally moveable in a plane parallel to the hinge plate provide an open position accommodating access to the pins and a closed position preventing inadvertent displacement of the pins from the apertures.